On Picturing a Candle: The Prehistory of Imagery Science - MacKisack, Matthew; Aldworth, Susan; Macpherson, Fiona; Onians, John; Winlove, Crawford; Zeman, Adam (Frontiers in Psychology, 2016)
The past 25 years have seen a rapid growth of knowledge about brain mechanisms involved in visual mental imagery. These advances have largely been made independently of the long history of philosophical – and even psychological – reckoning with imagery and its parent concept ‘imagination’. We suggest that the view from these empirical findings can be widened by an appreciation of imagination’s intellectual history, and we seek to show how that history both created the conditions for – and presents challenges to – the scientific endeavour. We focus on the neuroscientific literature’s most commonly used task - imagining a concrete object – and, after sketching what is known of the neurobiological mechanisms involved, we examine the same basic act of imagining from the perspective of several key positions in the history of philosophy and psychology. We present positions that, firstly, contextualise and inform the neuroscientific account, and secondly, pose conceptual and methodological challenges to the scientific analysis of imagery. We conclude by reflecting on the intellectual history of visualisation in the light of contemporary science, and the extent to which such science may resolve long-standing theoretical debates.